Outcomes and Complications of Ulnar Shortening Osteotomy: An Institutional Review. (September 2015) - Rajgopal, Raghav; Roth, James; King, Graham; Faber, Ken; Grewal, Ruby
Background: Ulnar impaction syndrome (UIS) is a common cause of ulnar wrist pain. Patients may be candidates for surgical intervention if nonoperative options are ineffective. At our institution, ulnar shortening osteotomy is the preferred procedure to manage this disorder. The purpose of this study was to present patient reported outcomes and complication rates of ulnar shortening osteotomy (USO) at mid-term follow-up. Methods: A retrospective chart review of 72 patients (75 wrists) obtained from our institutional database was performed. At a mean 32 months postoperatively, telephone interviews ( n =53) were performed for all patients who were available for follow-up. The patient-rated wrist evaluation (PRWE), a validated outcome tool, was completed and complications were reviewed. Results: Patient-rated outcomes were favorable; however, complications were frequent and included: delayed union (10/75, 13.3 %), nonunion (6/75, 8 %), and complex regional pain syndrome (5/75, 6.7 %). Ten patients (13.3 %) required revision surgery. Thirty-four patients (45.3 %) required hardware removal with 4/30 (11.4 %) of these patients experiencing refracture. Smokers (mean PRWE 67.1) and patients with workers' compensation claims (mean PRWE 64.9) reported higher residual pain and disability than their counterparts (mean PRWE 28.0; 25.2). Conclusions: General outcome measures were favorable. Smokers and patients with workers' compensation claims experienced significantly poorer outcomes. However, the incidence of nonunion and delayed union was higher than most reports in the literature. Furthermore, we demonstrated a high refracture rate (11.4 %) following removal of hardware.